Rancang Bangun Sistem Informasi Monitoring Organisasi Mahasiswa Berbasis Web Menggunakan Framework Codeigneter - Nufusi, Islahatun; Gunawan, Waliadi; Hidayanti, Nur; Kusnadi, Endang (Jurnal Ilmiah Sains dan Teknologi, 2023)
The Student Organization Monitoring Information System (SIMORA) is a student monitoring system for student organizations at Banten Jaya University using electronic device technology. Student organizations at the University of Banten Jaya currently in terms of administrative management such as correspondence, funding applications, proposals, accountability reports and announcements, activity information, and so on still use a manual system that still uses paper so it is vulnerable to data storage errors. All administrative activities will be archived and used as a reference in implementing activities for each student organization in the next period. The purpose of this research is to design a website for monitoring student organization activities and to help optimize the administrative process of student organizations through SIMORA. The system design method used in this research is using the Waterfall method so that it is easier to develop and use UML for visual system modeling. SIMORA is made website-based using the CodeIgniter framework. This student organization monitoring information system acts as a means of supporting the running of a web-based organization so that it can be accessed online with various service features that are mutually integrated with one another. This information system can facilitate the head of student affairs in disseminating information, disciplining student organizations regarding programs to be implemented, and supervising student organizations in terms of administration and student activities. This system can help discipline student organizations in submitting activities because, in the SIMORA system, they cannot propose activities if they are not in accordance with the Draft Activity Budget (RAK) this system also only enters submission data so as to minimize revisions to submissions.